Spatial and functional heterogeneity of follicular helper T cells in autoimmunity. (December 2019) - Seth, Abhinav; Craft, Joe
Highlights: Tfh cells drive isotype switch and affinity maturation of pathogenic autoantibodies. Tfh cell subsets acquire unique functional properties based on the cytokine milieu. T cells that help B cells localize to germinal centers or extrafollicular spaces. Tfh cells are therapeutic targets in autoimmune disease. Abstract : Follicular helper T cells provide signals that promote B cell development, proliferation, and production of affinity matured and appropriately isotype switched antibodies. In addition to their classical locations within B cell follicles and germinal centers therein, B cell helper T cells are also found in extrafollicular spaces – either in secondary lymphoid or non-lymphoid tissues. Both follicular and extrafollicular T helper cells drive autoantibody-mediated autoimmunity. Interfering with B cell help provided by T cells can ameliorate autoimmune disease in animal models and human patients. The next frontier in Tfh cell biology will be identification of Tfh cell-specific pathogenic changes in autoimmunity and exploiting them for therapeutic purposes.